2017
DOI: 10.1016/j.jcot.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

The importance of pelvic ring stabilization as a life-saving measure in pre-hospital – A case report commented by autopsy

Abstract: Keywords:Unstable pelvic ring Open book pelvic fracture Hemorrhagic shock A B S T R A C T Hip fractures with unstable pelvic ring have great morbidity and mortality rates. These fractures result from high energy trauma such as falls from heights, road accidents and collapsing structures or other similar mechanisms of action. We report the case of a 63 years old man, construction worker, who stood inside a ditch during a wall construction when he was surprised by this collapse, which resulted in direct trauma t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
(22 reference statements)
0
3
0
1
Order By: Relevance
“…Oko 3% svih preloma kostiju pripada disrupciji karličnog prstena [1]. Nastaju dejstvom mehaničke sile velike energije u saobraćaju, padom sa visine ili udarom mehaničkog oruđa.…”
Section: Uvodunclassified
“…Oko 3% svih preloma kostiju pripada disrupciji karličnog prstena [1]. Nastaju dejstvom mehaničke sile velike energije u saobraćaju, padom sa visine ili udarom mehaničkog oruđa.…”
Section: Uvodunclassified
“…Essas fraturas resultam de traumas de alta energia, como quedas de altura, acidentes rodoviários e estruturas em colapso ou outros mecanismos semelhantes de alta ação cinética. As fraturas pélvicas resultantes desses cenários são frequentemente associadas a lesões abdominais, pélvicas ou torácicas 1 .…”
unclassified
“…A recently published article in your journal emphasized the importance of pelvic ring stabilization in the management of an open-book fracture. 1 It has been emphasized that, because of the significant morbidity and mortality associated with this type of trauma, the early application of a pelvic circumferential compression device (PCC) can achieve fracture stabilization and reduce hemodynamic deterioration. 2,3 The conclusion by Durão, et al was that a modest maneuver with equipment such as a bedsheet can be effective in fracture stabilization.…”
mentioning
confidence: 99%
“…2,3 The conclusion by Durão, et al was that a modest maneuver with equipment such as a bedsheet can be effective in fracture stabilization. 1 If one considers the bedsheet as the "strap" of a hemorrhagecontrol tourniquet, then it must also be hypothesized that the introduction of a large windlass, seen with commercial tourniquets, would improve improvised PCC efficacy. One study involving a simulated extremity hemorrhage revealed that the introduction of a windlass to a circumferential strap significantly stopped "bleeding" compared to a strap alone and the use of this adjunct has received acceptance in wilderness and military medical practice under specific circumstances.…”
mentioning
confidence: 99%